2010
DOI: 10.1186/1749-8104-5-14
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehogexpressing and responding cells generate neuronal diversity in the medial amygdala

Abstract: BackgroundThe mammalian amygdala is composed of two primary functional subdivisions, classified according to whether the major output projection of each nucleus is excitatory or inhibitory. The posterior dorsal and ventral subdivisions of the medial amygdala, which primarily contain inhibitory output neurons, modulate specific aspects of innate socio-sexual and aggressive behaviors. However, the development of the neuronal diversity of this complex and important structure remains to be fully elucidated.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(113 citation statements)
references
References 69 publications
7
106
0
Order By: Relevance
“…As such, Cre is exclusively expressed in Gli1-expressing cells, thereby indicating the target cells of hedgehog signaling in these mice. 28,29 We found that, at 10 days after IRI, Cre was expressed in renal interstitial cells but not tubular cells. Double immunostaining revealed that Cre ( Figure 1J, red) was costained with vimentin (fibroblast marker) ( Figure 1J, green) but not CD45 (common leukocyte marker) or CD31 (endothelial cell marker) ( Figure 1J).…”
Section: Tubule-derived Shh Targets Interstitial Fibroblasts In Vivomentioning
confidence: 77%
“…As such, Cre is exclusively expressed in Gli1-expressing cells, thereby indicating the target cells of hedgehog signaling in these mice. 28,29 We found that, at 10 days after IRI, Cre was expressed in renal interstitial cells but not tubular cells. Double immunostaining revealed that Cre ( Figure 1J, red) was costained with vimentin (fibroblast marker) ( Figure 1J, green) but not CD45 (common leukocyte marker) or CD31 (endothelial cell marker) ( Figure 1J).…”
Section: Tubule-derived Shh Targets Interstitial Fibroblasts In Vivomentioning
confidence: 77%
“…The only exception is Lhx6 in amphibians since no published data have been found. As noted above, based on these criteria many neurons of the medial amygdala of mammals were proposed to originate either in the pallidal subdivision or the preoptic subdivision [García-López et al, 2008], which was later shown by fate mapping analysis [Hirata et al, 2009;Waclaw et al, 2010;Carney et al, 2010;Bupesh et al, 2011a]. The use of these criteria has also helped to support the identification of a 'medial amygdala' in sauropsids Moreno et al, 2010] and amphibians [Moreno et al, 2008a] ( fig.…”
Section: Pallial Amygdala In Sauropsids and Amphibiansmentioning
confidence: 95%
“…2 ) [Flames et al, 2007;García-López et al, 2008] but also shows expression of other transcription factors such as Dbx1 [Hirata et al, 2009]. Based on gene expression profiles, migration assays, and genetic fate maps, the preoptic area has been shown to produce cells for the medial amygdala [García-López et al, 2008;Hirata et al, 2009;Carney et al, 2010;Bupesh et al, 2011a]. It appears that the neurons originate specifically in the commissural preoptic subdivision [Bupesh et al, 2011a] and that neurons reach primarily the anterior and posteroventral amygdala, where Shh-expressing and Dbx1-lineage cells are principally found ( fig.…”
Section: Development and Evolution Of The Amygdalamentioning
confidence: 99%
“…In recent years, the embryonic commissural PO, characterized by expression of Nkx2.1, Shh and Lhx7 at the ventricular zone and mantle, has emerged as a major source of neurons for the medial extended amygdala (mouse: García-López et al [2008], Carney et al [2010] and Bupesh et al [2011b] and chicken: Me-dina [2008, 2009] and reviews by Medina et al [2011] and Abellán et al [2013]). More recently, the embryonic commissural PO was also shown to produce a minor subpopulation of catecholaminergic neurons for the EAce and St in mice [Bupesh et al, 2014], and a similar contribution was also suggested to occur in chicken ( fig.…”
Section: Cells Of Po Origin In the Eacementioning
confidence: 99%